Modification of Clay Soil Permeability with Palm Shell Ash for Road Subgrade Repair - Debby Endriani; Nova Juliana; Nor Faizah Bawadi (Journal of Infrastructure and Civil Engineering, 2026)
The subgrade in Paloh 80, Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency, is a fine-grained clay with low stability, making it unsuitable for use as a road subgrade without stabilization. Therefore, stabilization efforts are needed to improve its technical properties. This study aims to analyze the effect of adding palm shell ash (ACS) on changes in the permeability coefficient of clay soil. The research method used is a laboratory experiment with variations in ACS mixtures at 0%, 4%, 6%, 8%, 10%, and 12% of the soil's dry weight under optimum water-content conditions. The stabilization process involves mixing clay soil with palm shell ash in varying proportions, followed by testing in accordance with ASTM standards, specifically the falling-head permeability test. The results show that adding palm shell ash significantly reduces the permeability coefficient of clay soil. The original soil permeability value of 8.339 × 10^(-8) cm/s decreased to 4.355 × 10^(-8) cm/s in the 12% mixture. This decrease was caused by the palm shell ash filler, which filled soil pore spaces, thereby inhibiting water flow. The results showed that the addition of ACS significantly reduced the permeability coefficient of clay soil. The original soil permeability value of 8.339 × 10^(-8) cm/s decreased to 4.355 × 10^(-9) cm/s in the 12% mixture. This decrease was caused by the ACS filler, which filled soil pore spaces, thereby inhibiting water flow. Thus, palm shell ash has potential as an environmentally friendly stabilization material to improve the quality of road subgrades.